Comparison of energy rationing systems for late gestation ewes: Impacts on ewe and lamb performance. Issue 8 (1st August 2016) - Campion, F. P.; McGovern, F. M.; Lott, S.; Fahey, A. G.; Creighton, P.; Boland, T. M.
Abstract: The objectives of this study were 1) to compare the effects of a ME (AFRC, 1993 ) or a NE (Jarrige, 1989 ) system for rationing ewes during late gestation on ewe and progeny performance and 2) to investigate incremental increases in NE allocation above 100% of recommendation during late gestation on ewe and progeny performance. Fifty-two twin-bearing ewes ( n = 13 per treatment) were rationed to either 100% of recommended ME requirements (100% ME) or 100, 110, or 120% of recommended NE requirements (100% NE, 110% NE, and 120% NE) from d 112 of gestation to parturition. Mean energy intake, measured as ME and NE, from Day 112 of gestation to parturition was higher in all NE treatments compared with 100% ME ewes ( P = 0.01). Ewes offered the 3 NE treatments had a higher live weight at parturition compared with 100% ME ewes ( P = 0.02), with 100% NE and 120% NE ewes still being heavier than 100% ME ewes at 35 d postpartum ( P = 0.02). Increasing NE allowance resulted in a linear decrease in the level of BCS loss prepartum ( P = 0.01) and a linear increase in the level of BCS loss postpartum ( P = 0.01). There was no difference observed between any of the treatments in total colostrum produced to 18 h postpartum ( P = 0.29) or in total colostrum intake to 18 h postpartum ( P = 0.27). Increasing maternal NE allowance led to a linear increase in lamb serum IgG concentration at 24 h postpartum ( P = 0.03). The estimated milk production of 120% NE ewes tended to be higher than all other treatments at wk 6 of lactation ( P = 0.08). Colostral SFA levels from 100% ME ewes was lower than that of all 3 NE treatments ( P = 0.01), and unsaturated fatty acid (UFA) levels in colostrum of the 100% ME ewes were lower than those of the 100% NE ewes ( P = 0.01). Cumulative levels of milk SFA, UFA, and MUFA did not differ between treatments ( P = 0.19). Lamb growth rates during the first 5 wk postpartum were unaffected by treatment ( P = 0.18) as were days to slaughter ( P = 0.34). It can be concluded that both ME and NE systems used in this study are appropriate for formulating ewe diets during late gestation. Increasing NE allocation above 100% altered the pattern of body reserve mobilization during late gestation and early lactation without observed variations in lamb performance during this time.